2006
DOI: 10.1128/jvi.02658-05
|View full text |Cite
|
Sign up to set email alerts
|

Role of Maternal Autologous Neutralizing Antibody in Selective Perinatal Transmission of Human Immunodeficiency Virus Type 1 Escape Variants

Abstract: Perinatal human immunodeficiency virus type 1 (HIV-1) transmission is characterized by acquisition of a homogeneous viral quasispecies, yet the selective factors responsible for this genetic bottleneck are unclear. We examined the role of maternal autologous neutralizing antibody (aNAB) in selective transmission of HIV-1 escape variants to infants. Maternal sera from 38 infected mothers at the time of delivery were assayed for autologous neutralizing antibody activity against maternal time-of-delivery HIV-1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 43 publications
9
89
3
Order By: Relevance
“…Although this is in contrast to previous results in subtype Binfected women (12), a recent study has yielded results similar to ours in that the neutralization breadth of maternal antibodies measured in infant samples did not correlate with protection from infection (36). Higher breadth of maternal neutralizing antibodies, at least for women infected with non-B subtypes, has thus shown no correlation with protection from MTCT.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Although this is in contrast to previous results in subtype Binfected women (12), a recent study has yielded results similar to ours in that the neutralization breadth of maternal antibodies measured in infant samples did not correlate with protection from infection (36). Higher breadth of maternal neutralizing antibodies, at least for women infected with non-B subtypes, has thus shown no correlation with protection from MTCT.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been reported that a virus that grew out in the presence of maternal antibodies in cell culture was more similar to the transmitted infant virus than the bulk maternal population, interpreted to indicate that a neutralization escape variant was transmitted (12). In that study, many of the infant isolates that could not be neutralized by maternal serum came from mothers who lacked autologous neutralizing antibodies, likely providing a second test of the lack of maternal neutralizing antibodies rather than testing the relative sensitivity of the transmitted virus.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies established this association (2,3). Several studies reported more potent HIV-1-neutralizing Ab responses in nontransmitting mothers compared with those in transmitting mothers (4) as well as transmission of neutralization escape variants (5)(6)(7)(8), yet other studies did not (9)(10)(11). These disparate results may be due to small cohort sizes, distinct timing of infant HIV-1 diagnosis, and inadequate control of major nonimmune risk modifiers of transmission.…”
Section: Introductionmentioning
confidence: 56%
“…9 In brief, patient plasma samples were heat inactivated at 568C for 30 min, and serial twofold dilutions in growth medium were incubated in 96-well plates for 90 min with viral isolates of 200 and 400 TCID 50 =ml in a humidified 5% CO 2 incubator at 378C. The 50 ml of 4Â10 6 =ml pooled HIVnegative donor PBMCs previously stimulated with PHA for 48 h was added to each well, which was 2Â10 5 =well [multiplicity of infection (MOI), 0.0005 and 0.0001].…”
Section: Autologous Neutralizing Antibody Assaymentioning
confidence: 99%
“…[6][7][8] However, NAB may be critical in the prevention of infection, as recently discussed. 9 In early highly active antiretroviral therapy (HAART) given to adults with primary infection, structured treatment interruption was associated with increases in ANAB and the maintenance of viral suppression. 10 Infants treated early with HAART (before 3 months of age) may respond to therapy with suppression of viremia, demonstrate increases in CD4…”
Section: Introductionmentioning
confidence: 99%